A comparison of referral patterns and characteristics of patients with first episode symptomatic genital HSV-1 and HSV-2 infections in Sheffield. Issue 3 (June 1996) - Nageswaran, A; Shen, R N; Craig, J; Kyi, T T; Priestley, C J; Kinghorn, G R
Abstract : OBJECTIVE: To ascertain factors associated with HSV-1 and HSV-2 isolates in patients attending a genitourinary medicine clinic with symptomatic first episode genital herpes (FEGH). DESIGN: Retrospective study. SUBJECTS: A total of 606 females and 333 males presenting with culture positive FEGH between 1990-94. SETTING: Department of Genitourinary Medicine, Royal Hallamshire Hospital, Sheffield, UK. METHODS: Group comparison of referral patterns, demographic data, prior and concurrent episodes of STD, recent partner change. RESULTS: HSV-1 infected patients of either sex were more likely to be general practitioner (GP) referred, to be white, and less likely to have had preceding STD episodes. Recent sexual partner change had occurred significantly more often in HSV-2 infected females but there was no similar difference between HSV-1 and HSV-2 infected males. CONCLUSION: The relative HSV-1:HSV-2 isolate ratio in FEGH is influenced by the referral patterns. HSV-1 isolates predominate in patients presenting to GPs who refer the patients to GUM clinics for accurate diagnosis, counselling, follow up and screening for other STDs.